Efeito de nanopartículas híbridas lipídico-poliméricas catiônicas carregadas com benznidazol em modelo in vitro de infecção por Trypanosoma cruzi - Medeiros, Thayse Silva (2024)
Chagas disease, also known as American Trypanosomiasis, is a neglected tropical illness caused by the hemoflagellate protozoan Trypanosoma cruzi. Currently, only two drugs, Benznidazole (BNZ) and Nifurtimox, have been approved for disease treatment, with BNZ being the only one authorized for use in Brazil. However, BNZ faces various limitations including low bioavailability and higher toxicity to the host. Parasite resistance to the treatment has been also reported. In this regard, nanotechnological formulations for drug delivery have emerged as a promising alternative to improve the pharmacological properties and bioavailability of this drug. In this study, we investigated the in vitro effectiveness of cationic PLGA-cholesterol hybrid nanoparticles loaded with BNZ as a drug-delivery platform against T. cruzi. The nanoprecipitation method was used to obtain the hybrid nanoparticles (HNP), and their size, polydispersity index, and zeta potential were determined. Following PEI functionalization, the size of the HNPs was less than 200 nm, with homogeneous particle distribution and a zeta potential ranging from -20 to +10. The efficiency of encapsulation was determined to be 40% for anionic HNPs, increasing to 54% for cationic counterparts. FTIR and XRD analyses corroborated the successful encapsulation of BNZ. Morphological characterization through scanning electron microscopy (SEM) demonstrated spherical-shaped particles, regardless of their composition. In vitro studies showed that nanoparticles are safe at the evaluated concentrations for cardiomyoblasts. Furthermore, compared to the free drugs, HNPs exhibited higher trypanocidal effects against intracellular amastigotes, as evidenced by IC50 values of <5.9 and 38.6, respectively. However, no statistical difference was observed between the trypanocidal activity of the anionic and cationic systems. Fluorescence microscopy images showed the internalization of HNPs from 5 minutes onward. Taken together, our results showed the successful development of HNPs, underscoring their potential as a promising platform for the delivery of therapeutic agents used in the treatment of Trypanosoma cruzi infection.